The Horns of Moses. Setting the Bible in its Historical Context - Thomas Römer (Collège de France, 2013)
Developments in literary methodologies and archaeology have led scholars to question the traditional conception of biblical chronology and historiography. The starting point for Maximalist studies is the idea that the biblical story should simply be taken as true. However this position is indefensible from a scientific standpoint. Minimalists consider that everything began either during the Achaemenid period, around 400 years before our own era, or even later during the Hellenistic period. Th...